Analisa Pengaruh Hambatan Samping terhadap Kinerja Jalan Di Jalan Orang Kayo Pingai Kota Jambi - Syarwan Abdan; Amsori M Das; Susiana Susiana (Universitas Batanghari Jambi, 2022)
Increased volume of traffic flow will cause changes in traffic behavior of a road segment, especially on urban roads. This increase is caused by the increasing number of residents and the need for transportation facilities so that enough space is needed for traffic infrastructure such as roads, parking locations and so on. High road side activity has a major effect on road capacity and performance in an urban area. Among them such as pedestrians, road crossings, street vendors (Street vendors), slow-walking vehicles (rickshaws, bicycles, horse-drawn carriages), vehicles stopped carelessly (city transportation, inner-city buses), parking on the street (on street parking), and vehicles in and out of road-side land use activities. The purpose and purpose of the study conducted by this author is to find out the performance of the road against side obstacles. And the objectives can be described as follows, namely:To find out the volume of traffic, the amount of capacity and level of service on the road people kayo pingai during rush hour.To analyze the modeling of side barriers and road capacity of Kayo Pingai people using simple linear regression. As for the benefits that are expected and can be taken by the authors of the implementation of this study, including: Increase knowledge and insight into the characteristics of traffic and vehicle parking on the road body and know the various lalaulintas problems that occur in urban areas, especially on Jalan Orang Kayo Pingai.